ANALISIS PENGARUH FAKTOR INTERNAL EMITEN TERHADAP BAGI HASIL INVESTOR PADA OBLIGASI SYARIAH MUDHARABAH DI INDONESIA - Sri Rahayu; Isti Fadah; Novi Puspitasari (Universitas Jember, 2013)
This study aims to analyze the influence of internal factors of emitens that affect the investors profit-sharing to the mudharabah islamic bond in Indonesia. This study used an independent variable in the form of internal factors (debt ratio, current ratio, ROA and ROE) and the dependent variable in the form of profit-sharing mudharabah islamic bond investors. This research is using multiple linear regression analysis and using purposive sampling as the sampling method. The results showed that significantly affect the variable debt ratio (X1), current ratio (X2), ROA (X3) and ROE (X4) simultaneously to the profit-sharing mudharabah islamic bond investors. Partially, variable followed by current ratio, ROA, and ROE which significantly affect the results of profit-sharing mudharabah islamic bond investors in Indonesia. Keywords: Mudharabah Islamic bond of profit-sharing, financial ratios, purposive sampling and multiple linier regression analysis.